Impact of Smoking and Smokeless Tobacco on Salivary Flow Rate, pH Levels and Salivary Electrolytes - Syeda Sadia Hassan; Syed Hussain Askary; Syed Mohammad Ahmed Bukhari; Amir Akbar Shaikh; Syed Akbar Abbas Zaidi; Abubakar Abdullah; Hassan Shahid (Pakistan Journal of Medicine and Dentistry)
Background: Tobacco use, both in smoked and smokeless forms, poses a significant threat to public health. The specific impact of tobacco use on the parameters of saliva still needs to be explored. Hence, the current study aimed to identify the impact of smoking and smokeless tobacco on salivary flow rate, pH levels, and salivary electrolytes.